Phase II Study of Olaparib (AZD‐2281) After Standard Systemic Therapies for Disseminated Colorectal Cancer. (19th January 2016) - Leichman, Lawrence; Groshen, Susan; O'Neil, Bert H.; Messersmith, Wells; Berlin, Jordan; Chan, Emily; Leichman, Cynthia G.; Cohen, Steven J.; Cohen, Deirdre; Lenz, Heinz‐Josef; Gold, Philip; Boman, Bruce; et al.
Abstract : Background: Effective new agents for patients with colorectal cancer (CRC) with disease progression during standard therapy regimens are needed. We hypothesized that poly ADP ribose polymerase (PARP) inhibitor therapy in patients with CRC and inefficient tumor DNA repair mechanisms, such as those with high‐level microsatellite instability (MSI‐H), would result in synthetic lethality. Methods: This was an open‐label phase II trial testing olaparib 400 mg p.o. b.i.d. for patients with disseminated, measurable CRC failing standard therapies with centrally confirmed tumor MSI status. The primary endpoint was the tumor response, assessed by RECIST, version 1.0. The secondary endpoints were safety/toxicity, progression‐free survival (PFS), and overall survival (OS). Results: Thirty‐three patients (20 microsatellite stable [MSS], 13 MSI‐H) were enrolled. The median age for all patients was 57 years and for MSS and MSI‐H patients was 51 and 61 years, respectively. All patients received at least one 28‐day cycle of olaparib. No patient had a complete or partial response. Nausea (48%), fatigue (36%), and vomiting (33%) were the most commonly reported treatment‐related adverse events. The median PFS for all patients was 1.84 months. No statistically significant differences were found in the median PFS or OS for the MSS group compared with the MSI‐H group. Conclusion: Single‐agent olaparib delivered after failure of standard systemic therapy did not demonstrate activity for CRC patients, regardless of microsatellite status. Future trials, testing PARP inhibitors in patients with CRC should focus on the use of DNA‐damaging chemotherapy and/or radiation therapy, combined with PARP inhibitors, remembering the toxicity reported in the present study. Implications for Practice: Microsatellite instability (MSI‐H) colorectal tumors exhibit hypermethylation in tumor mismatch repair genes, or have mutations in one or more of these genes resulting from a germ‐line defect (Lynch syndrome). PARP inhibitors such as olaparib are most effective in tumors associated with inability to repair DNA damage. However, in this trial, single agent olaparib failed to elicit responses in patients with MSI‐H colorectal tumors, and in those with microsatellite‐stable tumors. It is possible that by adding olaparib to radiation therapy, or to a systemic DNA damaging agent, tumor lethality could be obtained. However, the price would be increased toxicity. Abstract : Effective new agents for patients with colorectal cancer (CRC) with disease progression during standard therapy regimens are needed. Single‐agent olaparib delivered after failure of standard systemic therapy did not demonstrate activity, regardless of microsatellite status. Future trials testing poly ADP ribose polymerase (PARP) inhibitors against CRC should focus on DNA‐damaging chemotherapy and/or radiation therapy, combined with PARP inhibitors.